Chronology and sedimentology of a new 2.9 ka annually laminated record from South Sawtooth Lake, Ellesmere Island in this NOAA depository: https://www.ncdc.noaa.gov/paleo/study/33214. (15th October 2019) - Lapointe, Francois; Francus, Pierre; Stoner, Joseph S.; Abbott, Mark B.; Balascio, Nicholas L.; Cook, Timothty L.; Bradley, Raymond S.; Forman, Steven L.; Besonen, Mark; St-Onge, Guillaume
Abstract: Few annually laminated (varved) lacustrine records exist in the Arctic, but these high-resolution climate archives are needed to better understand abrupt climate change and the natural mode of climate variability of this sensitive region. This paper presents a new high-resolution 2900-year long varved lake sediment record from the Fosheim Peninsula, Ellesmere Island. The varve chronology is based on multiple varve counts made on high-resolution scanning electron microscope images of overlapping sediment thin sections, and is supported by several independent dating techniques, including 137 Cs and 210 Pb analysis, one optically stimulated luminescence age located close to the bottom of the composite sequence, and comparison between paleomagnetic variations of this record and the longest High-Arctic varve record, Lower Murray Lake, which confirms the reliability of the Sawtooth chronology. High-resolution backscattered images examined under a scanning electron microscope (SEM) were crucial to giving a more detailed view of sedimentation processes in the lake and thus help to delineate varves more precisely than in conventional image analysis. Fine-scale geochemical analysis reveals that lake sedimentation is mainly clastic and that elemental geochemistry is influenced by grain-size. Principal component analysis of multiple proxies and the coarse grain-size fraction of South Sawtooth Lake display similar fluctuations to the nearby Agassiz Ice Cap ∂ 18 O record, including lower values during the Little Ice Age cold period. These results show this new high-resolution and continuous record has a reliable varve chronology and is sensitive to temperature variability. South Sawtooth Lake's mean sedimentation rate of 1.67 mm a −1 is higher than any other sedimentary sequence in the High Arctic providing a unique opportunity for extracting new, high-resolution paleoclimatological and paleoenvironmental record in a region where few other records currently exist. Highlights: High-resolution scanning electron microscope images increase the reliability of varve-based chronology. The long-term decline in Sawtooth Lake and Agassiz δ 18 O records consistent with the progressive decrease in northern hemisphere insolation. Coldest conditions dominated during the Little Ice Age and culminated in early 18 th century. The sharp increase of the coarse grain-size in the turn of the 20 th century is coherent with the recent warming that reversed the long-term cooling trend.